Stuart R. Schräm. Ideology and Policy in China since the Third Plenum, 1978-84, Londres, Contemporary China Institute, School of Oriental and African Studies, University of London, viii + 81 pp. (Research Notes and Studies num. 6) - Cornejo Bustamante, Romer (Estudios de Asia y África, 1985)
-